Sex Differences in Synaptic Plasticity: Hormones and Beyond - Hyer, Molly M.; Phillips, Linda L.; Neigh, Gretchen N. (Frontiers in Molecular Neuroscience, 2018)
Notable sex-differences exist between neural structures that regulate sexually dimorphic behaviors such as reproductive and parenting behaviors. While these anatomical differences have been well-characterized, advancements in neuroimaging and pharmacology techniques have allowed researchers to identify differences between males and females down to the level of the synapse. Disparate mechanisms at the synaptic level contribute to sex-specific neuroplasticity that is reflected in sex-dependent behaviors. Many of these differences at the synapse are driven by the endocrine system and its impact on molecular signaling and physiology. While sex-dependent modifications exist at baseline, further differences emerge in response to environmental stimuli such as stressors. While some of these mechanisms are unifying between sexes, they often have directly opposing consequences in males and females. This variability is tied to gonadal steroids and their interactions with intra- and extra- cellular signaling mechanisms. This review focuses on the various mechanisms by which sex can alter synaptic plasticity, both directly and indirectly, through steroid hormones such as estrogen and testosterone. That sex can drive neuroplasticity throughout the brain, highlights the importance of understanding sex-dependent neural mechanisms of the changing brain to enhance interpretation of results regarding males and females. As mood and stress responsivity are characterized by significant sex-differences, understanding the molecular mechanisms that may be altering structure and function can improve our understanding of these behavioral and mental characteristics.